Public Health Response to Zika Virus Exposure of Air Force Members Deployed to Caribbean Islands, 2016. Issue 9 (1st September 2020) - Voss, Jameson; Dacey, Danny; Ruiz, Stefani; Burkhardt, Amanda; Pujolar, Alain; Swope, Christina; Lehman, Mark; Shaw, Tammy; Leon, Juan; Erich, Roger; Cowan, James; West, Carol; et al.
Abstract: Introduction: The emergence of Zika virus disease (ZVD) in areas of military operations provided a new opportunity for force health protection. ZVD infection had an estimated 4:1 asymptomatic-to-symptomatic ratio and can cause neurologic sequelae. Materials and Methods: We provide a brief report of a field investigation utilizing laboratory-based surveillance and survey instruments to characterize ZVD risk among personnel deployed to the Dominican Republic in support of Operation NEW HORIZONS (NH). Additionally, we describe a cluster of 3 ZVD cases among 8 aircrew on a short mission to St. Croix (U.S. Virgin Islands). Results: Following Operation NH, 6 of a total 189 deployed cohort members tested positive for ZVD by immunoglobulin M and confirmatory plaque reduction neutralization test (3.2%). Reverse transcription polymerase chain reaction testing in urine or serum was positive in 4 of those 6 cases. All 6 cases reported at least one symptom, with 5 reporting subjective fever and arthralgia and 4 reporting rash. Cases were less likely to have air-conditioned living quarters (odds ratio = 0.1; 95% confidence interval 0.02–0.77; P  < 0.03), but were otherwise similar to non-cases. Likewise, in St. Croix, 3/8 tested positive by immunoglobulin M and plaque reduction neutralization test for an attack rate of 38%. Similar to Operation NH, all three cases were symptomatic with subjective fever (67%), arthralgia (67%), and/or rash (100%). Conclusions: This field investigation identified differing, mission location-dependent ZVD attack rates and a 0:9 asymptomatic-to-symptomatic case ratio. As this was unexpected based on a previous report of a 4:1 ratio, it emphasizes the need to be cautious before generalizing outbreak characteristics between populations while also offering additional practical experience for force health protection.